The Combined Impact of Gender and Age on Post-traumatic Stress Symptoms, Depression, and Insomnia During COVID-19 Outbreak in China - Liu, Chengbin; Liu, Danxia; Huang, Ning; Fu, Mingqi; Ahmed, Jam Farooq; Zhang, Yanjun; Wang, Xiaohua; Wang, Yiqing; Shahid, Muhammad; Guo, Jing (Frontiers in Public Health, 2021)
The mental health problems might have been increased owing to the COVID-19 pandemic with the commencement of the year 2020, therefore, an epidemiological survey appraising the burden of mental health issues among the general population is imperative. This cross-sectional study attempts to reveal the underlying mental health conditions, such as Post-Traumatic Stress Disorder (PTSD), depression, and insomnia, relating to the pandemic situation, and to further examine the combined effects of gender and age on the COVID-19 related mental health consequences. An online survey was conducted among 2992 adults in China from February 1st 2020 to February 10th 2020. The study uses binary logistic regression to analyze the potential factors associated with PTSD, depression, and insomnia. The results indicate that the prevalence of PTSD, depression, and insomnia are 19.5%, 26.9%, and 19.6% respectively during the COVID-19. Men and women show different rates of PTSD and depression, whereas no insomnia is found in both males and females. The females above 50 years of age have a lower level of depressive symptoms (OR=0.448, 95%CI: 0.220-0.911, Cohen's d=-0.443) as compared with females aged 18-25; while the highest effect sizes for PTSD (OR=2.846, 95%CI: 1.725-4.695, Cohen's d=0.537) and the depression (OR=2.024, 95%CI: 1.317-3.111, Cohen's d=0.314) are seen in males aged 26 to 30. Besides gender, education, living conditions, direct exposure to COVID-19, the post mental and the physical health condition is related to PTSD, depression, and insomnia. Our study suggests that high-risk groups, especially those having two or more related factors and young men, should be the focus of mental health intervention.